40 Integrated model of patient factors, resectability score and surgical complexity index to predict surgical outcome in debulking surgery for advanced ovarian cancer. (13th November 2020) - Hogen, L; Laframboise, S; May, T; Ding, A; Bernardini, M
Abstract : Objectives: To assess integrated prediction model (IPM) including patient factors, radiological and surgical complexity scores, as a tool to predict optimal debulking (OD) in patients with newly diagnosed advanced ovarian cancer (AOC). Methods: Starting October-1-2018, all patients with newly diagnosed AOC were presented in designated ovarian cancer rounds. Decision for primary debulking (PDS) or neoadjuvant chemotherapy was made based on radiologic and clinical factors. For the IPM we used: 1. Patient factors score (Age, ECOG, albumin) 2. Resectability score: designated radiologists scored specific radiologic criteria (previously identified as associated with suboptimal debulking). 3. Surgical complexity index: surgeons scoring of anticipated procedures required to achieve OD. Surgical outcome, complications and time to chemotherapy were recorded. Results: Ninety-five patients met inclusion criteria (October-2018 to August-2019). Forty-four (47%) underwent PDS: 39 (89%) had optimal debulking: 12 to <1 cm and 27 to no visible residual disease. 5/44(11%) had 'open-and-close' procedure due to non-resectable disease at the time of surgery. Median Length of stay was 6 days, (1–14d), time from surgery to chemo was 25 days, (7–42d), and grade 3 complications were recorded in 9 patients (20%). Patients triaged to PDS were significantly younger (median 57 vs. 67, p<0.0001), had lower patient factors scores (median 0.5 vs 2 p<0.0001), lower resectability score (median 2 vs. 4, p<0.0001) and lower surgical complexity index (median 5 vs. 9 p<0.0001). Conclusion: IPM is an effective clinical tool in managing patients with newly diagnosed AOC, and can be utilized to select patients who will benefit from PDS.